2014
DOI: 10.1371/journal.pone.0096674
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Acute Respiratory Infections in Children in Guangzhou: A Three-Year Study

Abstract: Acute Respiratory Infections (ARI) are some of the most common human diseases worldwide. However, they have a complex and diverse etiology, and the characteristics of the pathogens involved in respiratory infections in developing countries are not well understood. In this work, we analyzed the characteristics of 17 common respiratory pathogens in children (≤14 years old) with ARI in Guangzhou, southern China over a 3-year period using real-time polymerase chain reaction. Pathogens were identified in 2361/4242 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
89
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(119 citation statements)
references
References 51 publications
20
89
10
Order By: Relevance
“…Flu was the second most frequently detected respiratory virus (9.3%). The age characteristics and monthly distribution of RSV and the seven respiratory viruses in Guangzhou during 2011-2016 were consistent with those in previous reports (Liu et al, 2014;Zhang et al, 2014). A total of 1514 patients were RSV-positive, 91.7% of whom were inpatients, significantly higher than outpatients (p < 0.01).…”
Section: Discussionsupporting
confidence: 89%
“…Flu was the second most frequently detected respiratory virus (9.3%). The age characteristics and monthly distribution of RSV and the seven respiratory viruses in Guangzhou during 2011-2016 were consistent with those in previous reports (Liu et al, 2014;Zhang et al, 2014). A total of 1514 patients were RSV-positive, 91.7% of whom were inpatients, significantly higher than outpatients (p < 0.01).…”
Section: Discussionsupporting
confidence: 89%
“…This proportion was similar to that reported in a previous study on the etiology of ARI in children aged younger than 5 years in Niger (78%), although on a limited number of samples . This finding was also consistent with those of other similar studies conducted in Africa (range 55%‐70%) and Asia (range 45%‐65%) …”
Section: Discussionsupporting
confidence: 80%
“…In patients, diagnosed with ARI the most frequently detected virus was HRV -33 (16.75%) ( Table 3). (8)(9)(10)(11)(12). Coinfections in this study were identified in a relatively small percentage of cases (3.15%).…”
Section: Clinical Characteristicsmentioning
confidence: 53%